2007
DOI: 10.1364/oe.15.012508
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electric field on laser induced damage threshold of multilayer dielectric gratings

Abstract: This paper studies gratings engraved in multilayer dielectric stacks for ultra high intensity laser compressors application. We design various grating profiles with high reflected efficiencies for 1780 l/mm multilayer dielectric gratings (MLD). Each grating is defined to exhibit a different electric field maximum value in the pillars of the grating. A damage testing facility operating at 1.053 mum, 500 fs pulse duration is used to damage test the parts manufactured from these designs. It is evidenced that for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
79
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 20 publications
5
79
0
Order By: Relevance
“…Samples tested differ by the grating profile in terms of pillar height and duty cycle. Damage testing was performed on the DERIC facility in S/1 mode, 10 Hz, with 100 sites tested and 100 shots per site [9]. During this study, we evidenced that damage threshold is proportional to 1/|E| 2 in the grating material, where |E| is the norm of the electric field in the solid material normalized by the norm of the electric field of the incoming wave [9].…”
Section: Multidielectric Pulse Compression Grating Damage Mechanismsmentioning
confidence: 92%
See 1 more Smart Citation
“…Samples tested differ by the grating profile in terms of pillar height and duty cycle. Damage testing was performed on the DERIC facility in S/1 mode, 10 Hz, with 100 sites tested and 100 shots per site [9]. During this study, we evidenced that damage threshold is proportional to 1/|E| 2 in the grating material, where |E| is the norm of the electric field in the solid material normalized by the norm of the electric field of the incoming wave [9].…”
Section: Multidielectric Pulse Compression Grating Damage Mechanismsmentioning
confidence: 92%
“…Damage testing was performed on the DERIC facility in S/1 mode, 10 Hz, with 100 sites tested and 100 shots per site [9]. During this study, we evidenced that damage threshold is proportional to 1/|E| 2 in the grating material, where |E| is the norm of the electric field in the solid material normalized by the norm of the electric field of the incoming wave [9]. This result was also observed on Mixed Metal Dielectric (MMLD) gratings that is basically a mirror constituted of a gold layer covered by some pairs of dielectrics with a low index top layer engraved [10].…”
Section: Multidielectric Pulse Compression Grating Damage Mechanismsmentioning
confidence: 99%
“…Damage test on gratings has shown that 4 J/cm 2 @ 500 fs can be reached for a 77.2 • angle of incidence [4]. During this campaign, transport mirrors were tested.…”
Section: Epj Web Of Conferencesmentioning
confidence: 99%
“…A laser induceddamage threshold (LIDT) characterization of gratings, i.e., the highest fluence value for which no damage is produced, is a main task to determine its applicability range. In the last years, LIDT in reflection multilayer dielectric gratings [1][2][3] and in mixed metal dielectric gratings 4 has been investigated by varying the material composition of the multilayer and by proving different grating profiles. The damage dynamics were established for a wide class of gratings, but only in the reflection geometry.…”
mentioning
confidence: 99%
“…For instance, damage at peak intensities due to interference effects has also been demonstrated in reflection gratings. [1][2][3][4] This damage mechanism is the main limitation on damage threshold for transmission gratings and for reflection gratings as well. Furthermore, the probabilistic model for Bragg incidence is determined substituting Eqs.…”
mentioning
confidence: 99%